Monitoring the snouts of local glaciers around Terra Nova Bay Station, (Victoria Land, Antarctica). - BONDESAN A.; MENEGHEL M.; SALVATORE, Maria Cristina (TERRA ANTARTICA PUBB., 2003)
Here are describe the frontal fluctuations of small local glaciers in the Tera Nova Bay area (Northern Victoria Land, Antarctica). The goal was to compare variations with environmental parameters and to establish a correlation between climate change and glacier behaviour. Althought small variations in the position of the snout of monitored glaciers have been observed, glaciers are in a steady state and there are no substantial change in their mass. The equilibrium is confirmed for long periods if we compare the present state of glaciers with their morphologies from aerial photographs fromthe 50s and 60s.